COGNITIVE-COMMUNICATIVE STRATEGIES OF KAZAKHSTANI LITERATURE: SPECIFICITY OF FORMATION AND FUNCTIONING - Altybayeva Saule Magazovna; Imposti Gabriella Elina (Scientific Journal of Pedagogy and Economics, 2020)
The article discusses the problem of the formation of the main cognitive-communicative strategies of the literary discourse of Kazakhstan. In the implementation of these strategies, a large role is played by cultural codes. The latter, as significant semiotic units of the text, are included in its conceptual core. Such concepts of the theory of cultural code as philosophical, ideological, conceptual core, ethnostereotype, heterotopic markers, detailed multicultural landscape and others receive terminological design. Cognition of the world and understanding of history, modernity, the possible future is often realized in a work through the universalization of the art world, multiculturalism, and the construction of complex narrative structures. The specificity of a historical narrative is analyzed with its characteristic capacious referential mode, involving the reader in the active communicative process of decoding narrated events and images. The heterotopic markers of myth-folklore units in the structure of a literary text are studied, the stability and iteration of traditional ethnocultural codes are noted. The bipolar tendency of ethnostereotyping and multicultural landscape of the art world is determined as an important cognitive-aesthetic strategy of literature in Kazakhstan. A multidimensional dialogical space of one or another cultural code is formed, an extension of its referential and epistemological connotations. The issues of sacralization, unversalization and profanation of the artistic space and time, various toposs, realities, and personalities are considered. The specificity of the narrative structure of the historical novel, diffusion methanarrative, is investigated. The content and functioning of such universal frequency codes as philosophemes and ideologemes are substantiated. By their dialogical and cognitive-communicative nature, philosophies, like mythologemes and folklorems, in a literary text come closer to the universals of culture. An additional result of such an immanent presence and subsequent development in the text of these philosophems (universals) is the complication of its genre, style nature. In connection with the implementation of the strategy of maximum metaphorization and universalization of the art world, the emergence of hybrid genres is justified: a novel-myth, a novel-requiem, a novelrevelation, and others. The inclusion in the literary text of a large amount of metatexts (diaries, notes, poems, translations) becomes an additional tool for constructing a complex system of coding and recoding information, specific translation of knowledge about the political, historical, cultural, legal, economic, systems, social stratification of the presented world spaces. A change in stereotype also finds a place in the paradigm of literary discourse. Some distinguished cultural codes (path, caravan), showing a strong attraction to each other, reinforce the philosophical and worldview depth of the narrative.